DISTORTED MIRROR OF ADVERTISING IN A MUSLIM SOCIETY: A study of television commercials by global companies in Pakistan - Shahid, Saima E. (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
Advertising of global business corporations is extensively investigated in various cultural settings for its modifying effect on host cultures, particularly promoting Western capitalist values. The same has raised concerns for Muslim societies where majority cultural values being derived from Islam are at loggerheads with Western values, a situation which may have ramifications for these societies. This study explored the very notion in Pakistan, and investigated the depiction of culturally consistent as well as inconsistent values in global companies’ television commercials running in the country. The content of prime time television ads by these companies from April 2017 to March 2018 (N=131) was analyzed for the use of advertising appeals, applying Hofstede’s dimensional model for national cultures and advertising appeals by Pollay (1983) with modifications to include regionally standardized appeals, in the perspective of distorted mirror theorizing by Pollay (1986). The descriptive and statistical analysis of content found majority value appeals used in these ads reflecting values contrary to the cultural tendencies of Pakistani society, including appeals for regional standardization. It also found significant association of major inconsistent appeals with commercials of products used by youth and women. Appeal family was found the most frequently used among culturally consistent appeals. Findings provided a unique way of extrapolating Pollay’s theorizing that mirror of advertising is distorted to the sellers’ interest. To cite this article (7th APA style): Shahid, S. E. (2021). Distorted Mirror of Advertising in a Muslim Society: A Study of Television Commercials by Global Companies in Pakistan. Journal Communication Spectrum: Capturing New Perspectives in Communication 11(2), 84-94.  http://dx.doi.org/10.36782/jcs.v11i2.2221